Vessel wall imaging with advanced flow suppression in the characterization of intracranial aneurysms following flow diversion with Pipeline embolization device. (5th January 2022) - Raz, Eytan; Goldman-Yassen, Adam; Derman, Anna; Derakhshani, Ahrya; Grinstead, John; Dehkharghani, Seena
Abstract : Background: High-resolution vessel wall MRI (VWI) is increasingly used to characterize intramural disorders of the intracranial vasculature unseen by conventional arteriography. Objective: To evaluate the use of VWI for surveillance of flow diverter (FD) treated aneurysms. Materials and methods: Retrospective study of 28 aneurysms (in 21 patients) treated with a FD (mean 57 years; 14 female). All examinations included VWI and a contemporaneously obtained digital subtraction angiogram. Multiplanar pre- and post-gadolinium 3D, variable flip-angle T1 black-blood VWI was obtained using delay alternating nutation for tailored excitation (DANTE) at 3T. 3D time-of-flight MR angiography (MRA) was also carried out. Images were assessed for in-stent stenosis, aneurysm occlusion, presence and pattern/distribution of aneurysmal or parent vessel gadolinium enhancement. Results: The VWI-MRI was performed on average at 361±259 days after the intervention. Follow-up DSA was performed at 338±254 days postintervention. Good or excellent black-blood angiographic quality was recorded in 22/28 (79%) pre-contrast and 21/28 (75%) post-contrast VWI, with no cases excluded for image quality. Aneurysm enhancement was noted in 24/28 (85.7%) aneurysms, including in 79% of angiographically occluded aneurysms and 100% of angiographically non-occluded aneurysms. Enhancement of the stented parent-vessel wall occurred significantly more often when aneurysm enhancement was present (92% vs 33%, p=0.049). Conclusion: Advanced VWI produces excellent depiction of FD-treated aneurysms, with robust evaluation of the parent vessel and aneurysm wall to an extent not achievable with conventional MRI/MRA. Gadolinium enhancement may, however, continue even after enduring catheter angiographic occlusion, confounding interpretation, and requiring cognizance of this potentially prolonged effect in such patients.